2007
DOI: 10.3892/ijo.30.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor binding protein-4 gene therapy increases apoptosis by altering Bcl-2 and Bax proteins and decreases angiogenesis in colorectal cancer

Abstract: Insulin-like growth factors are known to inhibit apoptosis and promote tumour angiogenesis. Previously we have shown that insulin-like growth factor binding protein-4 (IGFBP-4) gene therapy increased apoptosis and decreased mitosis in colon cancer. In this experiment we used HT-29 colon cancer cells to induce subcutaneous cancers in nude mice and administered either the mammalian expression vector with IGFBP-4 insert or vector only around the tumour site. Three weeks after gene transfer, tumours were harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Similar to these findings, IGFBP-4 exhibited differential inhibitory effects on histologically distinct tumor types as reports have documented the ability of IGFBP-4 to slow the growth of prostate and colon carcinomas, but showed no inhibitory activity in other tumor types such as renal cell carcinoma (23,24,27). Our findings may provide insight to explain in part, the variation in IGFBP-4 inhibitory activity on tumor growth, as angiogenesis within these different tumor types may be driven in part, by distinct growth factor signaling pathways.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to these findings, IGFBP-4 exhibited differential inhibitory effects on histologically distinct tumor types as reports have documented the ability of IGFBP-4 to slow the growth of prostate and colon carcinomas, but showed no inhibitory activity in other tumor types such as renal cell carcinoma (23,24,27). Our findings may provide insight to explain in part, the variation in IGFBP-4 inhibitory activity on tumor growth, as angiogenesis within these different tumor types may be driven in part, by distinct growth factor signaling pathways.…”
Section: Discussionsupporting
confidence: 72%
“…Importantly, studies have shown reduced levels of IGFBP-4 in malignant colon cancer as compared with normal colon tissues and, in addition, increasing the expression of IGFBP-4 in prostate and colon cancer cells slowed the growth of these tumors in vivo (23,24). Recently, we showed reduced levels of IGFBP-4 are expressed in human biopsies of metastatic melanoma as compared with primary melanoma (25).…”
mentioning
confidence: 99%
“…In contrast to our findings in an orthotopic model of breast cancer where wild-type IGFBP4 had no effect on tumour growth, wild-type IGFBP4 inhibited tumour growth in non-orthotopic murine models of colon cancer and prostate cancer where transfected cells were implanted subcutaneously (Damon et al, 1998;Durai et al, 2007). However, subcutaneous expression of the PAPP-A protease may be quite different to that in either the colon or the prostate gland.…”
Section: Discussioncontrasting
confidence: 55%
“…The ratio of Bcl2 to Bax can be a marker to indicate the level of apoptosis. 33 Our study shows that IGF-I reduces the muscle cell apoptotic level significantly and the PI3K inhibitor neutralise IGF-I action on apoptosis but p38 MAPK inhibitor has not affected apoptotic level. All these data suggest that IGF-I prevents cell from apoptosis through the PI3K/Akt and ERK1/2 MAPK pathways, but not via the p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 85%
“…32 Bax and Bcl-2 are two main proteins to mediate Mt membrane permeability. 33 Bax is a pro-apoptotic protein, which forms a trans-membrane pore across the outer Mt membrane, leading to loss of membrane potential and enhances apoptosis. Bcl-2 is an anti-apoptotic protein, which prevents the pore formation and cell death.…”
Section: Discussionmentioning
confidence: 99%